Effect of Recove ointment on pain in mothers susceptible to infection of cesarean scar - Poopak Karimi Yekta; Mahin Tafazzoli; Masoumeh Mirteimouri; Hasan Rakhshandeh; Habibollah Esmailei (Mashhad University of Medical Sciences, 2021)
Introduction: Postoperative pain including cesarean section is a source of concern for many pregnant women, as it can cause adverse effects on the wound healing process, especially in mothers prone to infection who require special care for better wound repair. Therefore, this study was performed with aim to investigate the effect of Recove ointment on pain in mothers with cesarean section who are susceptible to infection.  Methods: This two-group triple-blind controlled randomized trial was performed on 80 women with cesarean section who were eligible to participate in the study in Mashhad Omolbanin hospital in 2019. The subjects were placed in two groups of intervention and placebo. They used the ointment for 10 consecutive days. The pain intensity was assessed on the basis of visual analogue scale (VAS) in the days before intervention and 3, 5, and 10 days after cesarean section. Statistical analysis was performed using SPSS statistical software (version 21). Independent T-test, Mann-whitney u test, K-squared test and variance analysis were utilized for repeated data. A p-value of <0.05 was taken as significant. Results: During the ten days of follow-up, the intervention and placebo groups were not homogenous in terms of the variables of duration of walking (p= 0.002), sitting position (p= 0.03), and carbohydrate share (p= 0.04). In general, the pain scale was significantly different in the intervention and placebo groups which showed reduction of pain in the intervention group (p <0.001). Conclusion: Due to the presence of effective compounds, Recove ointment can significantly reduce the pain severity of the cesarean scare in mothers who are susceptible to infection.